Optimization of parameters in three dimensional printing objects with fused deposition modeling technology against geometry accuracy - Wilza, R.; ., Iskandar; Seprianto, Dicky; Adesta, Erry Yulian Triblas (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Dimensional printing object to produce accurate geometry in accordance with the planned. The process parameters investigated are layer height, print speed, perimeter shells and polishing time. Test specimens made with polymaker polysmoothTM material refer to ASTM D995-08 using 3D Printer type Fused Deposition Modelling (FDM). The measurement data were analyzed using ANOVA with design type 2 factorial level and design 4 factorial interactions (4FI) modelled by Design Expert® software. The result of ANOVA is known that the factors significantly (α = 0.05) have an effect on the geometry of 3D printing object and the optimum parameter combination that is height layer=0.14 mm, print speed=51.73 m s, perimeter shells=3 mm with polishing time=20 minutes. © BEIESP.